2011
DOI: 10.2139/ssrn.1968479
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomic Vulnerability and Disagreement in Expectations

Abstract: Non-technical summary 1 Introduction 2 Literature review 2.1 Heterogeneity, leverage and volatility 2.2 Social value of public information 2.3 Disagreement and uncertainty 2.4 Forecasting and early warning systems 3 Data and econometric methodology 3.1 Data 3.2 Regime-switching models with endogenous transition probabilities 4 Empirical fi ndings 4.1 Real activity 4.2 Volatility in stock markets 4.3 Stochastic simulations 4.4 Out-of-sample forecasting 5 Conclusions References Appendix CONTENTS 4 ECB Working Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…A recently growing body of literature suggests that individual experiences influence inflation expectation formation-a significant departure from the theoretical assumption that expectations draw from objective evaluations of the economy ("full information rational expectations"). Macroeconomic modeling literature has demonstrated that heterogeneity in consumer expectations can generate over-investment in real assets (Sims, 2009) impact the economy's vulnerability to exogenous shocks (Badarinza & Buchmann, 2011), and make shocks more persistent (Pedemonte et al, 2023).…”
Section: Partisan Perspectives On Inflation: Exploring Bias In Econom...mentioning
confidence: 99%
“…A recently growing body of literature suggests that individual experiences influence inflation expectation formation-a significant departure from the theoretical assumption that expectations draw from objective evaluations of the economy ("full information rational expectations"). Macroeconomic modeling literature has demonstrated that heterogeneity in consumer expectations can generate over-investment in real assets (Sims, 2009) impact the economy's vulnerability to exogenous shocks (Badarinza & Buchmann, 2011), and make shocks more persistent (Pedemonte et al, 2023).…”
Section: Partisan Perspectives On Inflation: Exploring Bias In Econom...mentioning
confidence: 99%